Peran Social Enterprise sebagai Inovasi Pengentasan Kemiskinan di Indonesia - Rafi Aufa Mawardi; Muhammad Rizki Pratama (Jurnal Studi Inovasi, 2023)
Social enterprise is an innovation in the field of business that plays a role in alleviating the problem of poverty. This article examines the role of social enterprise in overcoming the complexity of poverty problems in Indonesia. This study uses qualitative research methods with a literature study approach and social functioning theory as an analytical framework. This study found that there are four fundamental faces of poverty in Indonesia, namely high population growth, escalating unemployment rates, low levels of education, and unequal distribution of income. Researchers analyze that social enterprises exist as external parties whose role is to assist the government in overcoming poverty problems. This can be seen from several functional roles, such as conducting community empowerment, providing microfinance services, and providing free education. Keywords: Social Enterprise, Poverty, Innovation